2017
DOI: 10.1002/hep.29308
|View full text |Cite
|
Sign up to set email alerts
|

High hepatitis C cure rates among black and nonblack human immunodeficiency virus–infected adults in an urban center

Abstract: Background Hepatitis C virus (HCV) cure rates have been similar in patients with and without HIV co-infection; however, in the ION-4 study, black patients treated with ledipasvir/sofosbuvir were significantly less likely to achieve cure (90%) compared to non-black patients (99%). There are limited real world data on the effectiveness of oral direct acting antivirals (DAAs) in predominantly minority HIV/HCV co-infected populations. Methods We analyzed HCV treatment outcomes among 255 HCV co-infected patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
4
34
0
1
Order By: Relevance
“…Nevertheless, in patients with liver cirrhosis, we found no significant difference in HCV cure rate between HCV-monoinfected and HIV/HCV-coinfected individuals. Our results are supported by several studies with various treatment regimens in HIV/HCV-coinfected patients which also reported similar SVR rates in HIV/HCV-coinfected patients including those at more advanced fibrosis stages compared with HCV mono-infected patient groups [10][11][12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, in patients with liver cirrhosis, we found no significant difference in HCV cure rate between HCV-monoinfected and HIV/HCV-coinfected individuals. Our results are supported by several studies with various treatment regimens in HIV/HCV-coinfected patients which also reported similar SVR rates in HIV/HCV-coinfected patients including those at more advanced fibrosis stages compared with HCV mono-infected patient groups [10][11][12].…”
Section: Discussionsupporting
confidence: 88%
“…recently described a relationship between successful HIV RNA suppression to < 20 copies/mL and high SVR rate in coinfected patients. This effect may be driven by a higher adherence to medical treatment in these individuals as well as frequent and continuous relationship with health care professional with and support from a health care professional trained in infectious diseases . These results support our findings that HIV infection is not independently associated with a worse SVR12.…”
Section: Discussionmentioning
confidence: 99%
“…The overall SVR12 rate is in line with other evaluations of LDV/SOF efficacy in HIV/HCV co-infection, both in the ION-4 clinical trial [10] and in clinical cohort studies [13][14][15][16][17]. However, ION-4 reported a significantly lower SVR12 for black compared with non-black participants (90% and 99%, respectively).…”
Section: Discussionsupporting
confidence: 85%
“…Combined analysis of the ION-1-3 (HCV mono-infection) and ION-4 (HIV/HCV co-infection) studies in 865 participants found that LDV/SOF efficacy was not affected by the presence of HIV infection [12]. Clinical cohort studies have demonstrated high SVR12 rates for LDV/SOF treatment in HIV/HCV co-infected individuals, consistent with clinical trial findings [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 66%
“…Moreover, HCV cure rates may be lower in persons who switch antiretroviral therapy (ART) to accommodate DAAs (Falade-Nwulia et al, 2017)…”
mentioning
confidence: 99%